Examining Bdellovibrio bacteriovorus cell division processes and their metabolic cues during predation - Ray, Luke (2022)
Bdellovibrio bacteriovorus is a predatory bacterium that invades and digests other Gram-negative bacteria in its host dependent (HD) lifestyle. This predator traverses the outer membrane and digests a pore in the cell wall of the prey cell; it then enters the inner periplasm, sealing the pore and outer membrane, and establishing itself. Through modification of the host cell wall, the prey is rounded forming a bdelloplast. From the inner periplasm, B. bacteriovorus digest the host biomass sequentially and uses it to fuel their own growth, undergoing filamentous growth in the bdelloplast. Once prey nutrients have been consumed, the filament undergoes septation to create a variable number of progeny. This number is dependent on the available resources from the bdelloplast and can be odd or even. Following on from former PhD student David Milner’s work, my study focussed on the interaction partners of DivIVA, using pairwise Bacterial Two Hybrid (BTH) assays and then constructing a BTH library. Additionally, I investigated the divIVA operon with bioinformatics and fluorescent microscopy. Finally, while shielding from COVID-19, I bioinformatically analysed the division and cell wall (dcw) cluster of B. bacteriovorus and produced a phylogenetic tree for a study on its deacetylases, which includes lysozymes specific to prey entry and exit. DivIVA is a protein initially studied in Firmicutes, such as Bacillus subtilis. Its homologues have been implicated in regulating sporulation, cell morphology, apical growth, and several other processes in multiple, mainly Gram-positive, bacteria. Milner previously showed that DivIVA in B. bacteriovorus had roles in cell morphology and, potentially, septal site selection. I continued work on this protein by testing for interacting partners of DivIVA using pairwise BTH. This revealed a potential network of interactions that connect the roles of DivIVA with amino acid and cofactor Pyridoxal 5’-Phosphate (PLP) homeostasis, as well as chromosome partitioning. This involved proteins transcribed from neighbouring genes bd0466 and bd0465; YggS, for PLP homeostasis, and pyrroline 5-carboxylate reductase, for proline synthesis. Further interactions were found between Bd0465 and the canonical chromosome partitioning protein ParA3. This led to me investigating unknown interaction partners through the construction and use of a BTH library. This found several potential interacting proteins. A TrmJ homologue suggests crosstalk between DivIVA and the oxidative stress response, a link that has previously been found in Mycobacterium tuberculosis and Streptococcus suis. A MenE homologue was also identified as a potential interactor; this functions in menaquinone biosynthesis, a compound used in the electron transport chain. In Gram-negative bacteria, it is used for respiration in low oxygen environments, which could be emulated by the bdelloplast. During the pandemic and shielding from COVID-19, I analysed the dcw cluster of B. bacteriovorus. In rod shaped bacteria, the dcw cluster is a highly conserved region of the genome containing an operon encoding division, septation and cell wall synthesis proteins, including FtsZ. Both the genes and the order in which they are transcribed is conserved among bacteria, however, B. bacteriovorus have fifteen genes inserted into the cluster, fragmenting the ancestral operon. Investigating these genes shows varying roles for the encoded proteins. These include amino acid and nucleotide synthesis and homeostasis, stress response and DNA repair, and outer membrane lipid synthesis proteins. Finally, I produced a phylogenetic tree for a publication on the family of deacetylases that target deacetylated GlcNac. B. bacteriovorus modify the prey cell wall upon invasion, deacetylating GlcNAc. This serves to soften the wall and prevent other B. bacteriovorus from invading. Three deacetylases, which target the cell wall, were identified and one, DslA, was shown to lyse the bdelloplast at the end of the HD cycle. My phylogenetic analysis shows that DslA is related to lysozymes in several α-proteobacteria, including some plant root symbiotes, as well as some β- and γ-proteobacteria. Altogether, these results show complex regulation of division and septation in this predatory bacterium. This study primes further investigation into the crosstalk between division and other systems during the growth phase of B. bacteriovorus in the bdelloplast, while also identifying several novel metabolic interactions of DivIVA that can be further studied.